(3TQM GdCQHYjf MOjKG GdfHhjIs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CQSd QShdg HGdgOi CQOJ Cf CUfa QSGdI aj gPG GdHGH CejR ajgG GdbTQ Yf GddHGH hCHjf GdSff GdeJQhcI GdKGHJI HGdCMGOjK LeY CQHYjf MOjKG ef GdSffs
(3BNQgG (B:s
(3hbhd GdeDPf HdG dMf hdG JZf hGdYGOI aj ReGffG Cf ScJ GdNWjH dCLd GdeDPf djJZfi HGdfZeGJ agPG bdH GdehVhY dZQV GdeUfhY hGdghdj GdeUfhY hGdQjGA GdeMXhQ agPg gPgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 61s
(3eYLe GdeDdajf (B3 / 176s
(3cTa GdXfhf (B1 / 54s
(3gOjI GdYGQajf (B2 / 252s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs